A review of marine oil sampling methods. Issue 1 (4th March 2022) - Kneeland, J. M.; Tcaciuc, A. P.; Tuit, C. B.; Wait, A. Dallas
Abstract: After an oil spill, collecting reliable and legally defensible oil samples is critical for determining oil sources and assessing environmental impacts. This review of guidance documents and the scientific literature identifies accepted practices for collecting oil samples in the marine environment for chemical analysis. Recommended sampling techniques differ depending on the form of the oil being sampled (e.g., oil sheens/slicks versus tar balls). Preventing sample contamination and collecting representative oil samples are crucial. Collecting suspected source and background samples is recommended for source identification. Guidance on quality control samples varies, but at minimum, blanks are required to meet study data quality objectives.